Utilization of Indonesian E-Modules Based on The ICARE Approach as An Innovation in Learning for Students - Asri, Milya Febrirurahmy; Cahyani, Isah; Kurniawan, Khaerudin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to design and implement an Indonesian e-module based on the ICARE approach, which includes the stages of Introduction, Connection, Application, Reflection, and Extension. The method in this study was research and development (R&D) with the ADDIE model. The stages conducted in this study were (1) needs analysis, (2) design, (3) product development, (4) implementation or trial, and (5) evaluation. The validity of the product was assessed by three experts in the fields of material, language, and media. The calculation of the data in this study was analyzed using a questionnaire with a Likert scale method. The response trial was conducted with junior high school students in grade VIII from 3 schools in Batam City. Based on the test results, it was obtained a score of 4.58 with a validity level of 89%. It provides evidence that the implementation of e-modules based on the ICARE approach in an educational environment can increase the effectiveness of Indonesian learning. Students can learn independently and collaboratively, and develop critical skills such as problem-solving, analysis, and synthesis of information.